# Technically Exists

## Theorem $\mu$-1

The mu factorial has the same growth rate as the Ackermann-Péter function in terms of dominance over translations.

$n\mu! \eqv A(n, n)$

### Lemma $\mu$-2

$n\mu! > n + 4$ for all $n \in \N_0, n \ge 3$.

#### Proof

Base case:

\begin{align*} 3\mu! &= (3 \uparrow (2 \cdot (1 + 0))) \\ &= 9 \\ &> 7 \\ &= 3 + 4 \\ \end{align*}

Induction step for $n \ge 3$:

\begin{align*} (n + 1)\mu! &= (n + 1) \uparrow^{n - 1} (n\mu!) \\ &> (n + 1) \uparrow^{n - 1} (n + 4) &&\text{by the induction hypothesis} \\ &> (n + 1) + (n + 4) \\ &> n + 5 \\ \end{align*}

### Proposition $\mu$-2

$n\mu! > A(n, n)$ for all $n \in \N_0, n \ge 4$.

#### Proof

\begin{align*} n\mu! &= n \uparrow^{n - 2} ((n - 1)\mu!) \\ &> n \uparrow^{n - 2} (n + 3) &&\text{by Lemma } \mu\text{-2} \\ &> 2 \uparrow^{n - 2} (n + 3) \\ &> 2 \uparrow^{n - 2} (n + 3) - 3 \\ &= A(n, n) &&\text{by the Ackermann-Péter Closed Form Theorem} \\ \end{align*}

### Lemma $\mu$-3

$n\mu! < 2 \uparrow^n (n + 1)$ for all $n \in \N_0$.

#### Proof

Base cases:

\begin{align*} 0\mu! &= 0 \\ &< 2 \\ &= 2 \uparrow^0 (0 + 1) \\ 1\mu! &= 1 \\ &< 4 \\ &= 2 \uparrow^1 (1 + 1) \\ 2\mu! &= 2 \\ &< 16 \\ &= 2 \uparrow^2 (2 + 1) \\ \end{align*}

Induction step for $n \ge 2$:

\begin{align*} (n + 1)\mu! &= (n + 1) \uparrow^{n - 1} (n\mu!) \\ &< (n + 1) \uparrow^{n - 1} (2 \uparrow^n (n + 1)) &&\text{by the induction hypothesis} \\ &< (n + 1) \uparrow^{n - 1} ((n + 1) \uparrow^n (n + 1)) \\ &= (n + 1) \uparrow^n (n + 2) \\ &< (n + 2) \uparrow^n (n + 2) \\ &= (n + 2) \uparrow^{n + 1} 2 \\ &< 2 \uparrow^{n + 1} (n + 2) &&\text{by the Knuth Arrow Commutative Inequality} \\ \end{align*}

### Lemma $\mu$-4

$2 \uparrow^n m \le 2 \uparrow^n (m + 2) - 3$ for all $m, n \in \N_0$.

#### Proof

Base cases where $n = 0$:

\begin{align*} 2 \uparrow^0 m &= 2 \cdot m \\ &< 2 \cdot m + 1 \\ &= 2 \cdot m + 2 \cdot 2 - 3 \\ &= 2 \uparrow^0 (m + 2) - 3 \\ \end{align*}

Base cases where $m = 0$ and $n \ge 1$:

\begin{align*} 2 \uparrow^n 0 &= 1 \\ &= 4 - 3 \\ &= 2 \uparrow^n 2 - 3 \\ &= 2 \uparrow^n (0 + 2) - 3 \\ \end{align*}

Induction step for $m$, with the assumption that the lemma holds for $n$:

\begin{align*} 2 \uparrow^{n + 1} (m + 1) &= 2 \uparrow^n (2 \uparrow^{n + 1} m) \\ &\le 2 \uparrow^n (2 \uparrow^{n + 1} (m + 2) - 3) &&\text{by the induction hypothesis} \\ &\le 2 \uparrow^n (2 \uparrow^{n + 1} (m + 2) - 1) - 3 &&\text{by assumption} \\ &< 2 \uparrow^n (2 \uparrow^{n + 1} (m + 2)) - 3 \\ &= 2 \uparrow^{n + 1} (m + 3) - 3 \\ \end{align*}

Performing induction over $n$ completes the proof.

### Proposition $\mu$-3

$n\mu! < A(n + 1, n + 1)$ for all $n \in \N_0$.

#### Proof

Base cases:

\begin{align*} 0\mu! &= 0 \\ &< 3 \\ &= 2 + (1 + 3) - 3 \\ &= A(1, 1) \\ 1\mu! &= 1 \\ &< 7 \\ &= 2 \cdot (2 + 3) - 3 \\ &= A(2, 2) \\ 2\mu! &= 2 \\ &< 61 \\ &= 2 \uparrow (3 + 3) - 3 \\ &= A(3, 3) \\ \end{align*}

Induction step for $n \ge 2$:

\begin{align*} (n + 1)\mu! &= (n + 1) \uparrow^{n - 1} (n\mu!) \\ &< (n + 1) \uparrow^{n - 1} (2 \uparrow^n (n + 1)) &&\text{by Lemma } \mu\text{-3} \\ &< (2 \uparrow^n (n + 1)) \uparrow^{n - 1} (2 \uparrow^n (n + 1)) \\ &= (2 \uparrow^n (n + 1)) \uparrow^n 2 \\ &< 2 \uparrow^n (n + 3) &&\text{by the Knuth Arrow Theorem} \\ &\le 2 \uparrow^n (n + 5) - 3 &&\text{by Lemma } \mu\text{-4} \\ &= A(n + 2, n + 2) &&\text{by the Ackermann-Péter Closed Form Theorem} \\ \end{align*}

### Proof of Theorem $\mu$-1

By Proposition $\mu$-2, it cannot be the case that $n\mu! \gs A(n, n)$. By Proposition $\mu$-3, it cannot be the case that $n\mu! \gf A(n, n)$. Therefore, $n\mu! \eqv A(n, n)$.

### Referenced results

Ackermann-Péter Closed Form Theorem: Theorem 4 in Ackermann and the superpowers

Knuth Arrow Theorem: Theorem 3.1 in Knuth’s iterated powers

Knuth Arrow Commutative Inequality: Theorem 3.2 in Knuth’s iterated powers